1995
DOI: 10.1177/089686089501500308
|View full text |Cite
|
Sign up to set email alerts
|

Dialysate Markers of Peritoneal Tissue during Peritonitis and in Stable CAPD

Abstract: Objective To investigate whether dialysate concentrations of substances that are locally produced within the peritoneal cavity can be used to study the effects of inflammation on peritoneal tissue. Design We followed the appearance rates (AR) of concentrations of cancer antigen (CA) 125, phospholipids (PHL), hyaluronan (HA), and the procollagen peptides PICP (procollagen 1 C-terminal) and PIIINP (procollagen 3 N-terminal) in dialysate during peritonitis (8 consecutive days) and after recovery. Data were compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 26 publications
4
25
1
Order By: Relevance
“…Whether the in vitro experiments can be extrapolated to human situation remains questionable, as studies with more biocompatible dialysate solutions, but still containing glucose, almost universally demonstrated an increase in CA125 concentration in time (see below). CA125 is almost undetectable in lymphocytes, monocytes, granulocytes and fibroblasts [ 24 ], making peritoneal mesothelial cells the most likely source for local CA125 release during PD. In view of the constitutive release after confluence, it can be concluded that CA125 released from mesothelial cells can probably be used for follow-up of mesothelial cell mass in individuals.…”
Section: Ca125 As a Marker Of Mesothelial Cell Massmentioning
confidence: 99%
“…Whether the in vitro experiments can be extrapolated to human situation remains questionable, as studies with more biocompatible dialysate solutions, but still containing glucose, almost universally demonstrated an increase in CA125 concentration in time (see below). CA125 is almost undetectable in lymphocytes, monocytes, granulocytes and fibroblasts [ 24 ], making peritoneal mesothelial cells the most likely source for local CA125 release during PD. In view of the constitutive release after confluence, it can be concluded that CA125 released from mesothelial cells can probably be used for follow-up of mesothelial cell mass in individuals.…”
Section: Ca125 As a Marker Of Mesothelial Cell Massmentioning
confidence: 99%
“…In the Euro-PD-Balance trial, an increase in CA-125 and a decrease of hyaluronic acid concentrations in the drained dialysate during the use of PD-Balance was observed, and these changes disappeared again after switching to the classical glucose solution. Since CA-125 is considered to be a marker of mesothelial cell mass (58), and hyaluronic acid of mesothelial damage (59), this would point to an improved biocompatibility of this solution.…”
Section: And the New Solutions mentioning
confidence: 99%
“…( 60) and Ho‐dac‐Pannekeet and Krediet ( 61) have undertaken a survey of the various markers present in PD effluent, which may reflect the status of the peritoneal tissues, especially the mesothelium. At the moment, cancer antigen 125 (CA125) is likely to be the most useful marker of mesothelial cell mass or turnover in stable CAPD patients ( 62). However, no relationship has been found between dialysate CA125 concentrations and the permeability characteristics of the peritoneum ( 63).…”
Section: Chronic Fluid Overloadmentioning
confidence: 99%